The performativity of potential output: Pro-cyclicality and path dependency in coordinating European fiscal policies - Jakob Kapeller; Philipp Heimberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2016)
This paper analyzes the performative impact of the European Commission's model for estimating 'potential output', which is used as a yardstick for measuring the 'structural budget balance' of EU countries and, hence, is crucial for coordinating European fiscal policies. In pre-crisis years, potential output estimates amplified the build-up of private debt, housing bubbles and macroeconomic imbalances. After the financial crisis, they were revised downwards, which increased fiscal consolidation pressures. By focusing on the euro area's economies during 1999-2014, we identify two performative aspects of the potential output model. First, the political implications of the model led to a pro- cyclical feedback loop, reinforcing general economic developments. Second, the model has contributed to national lock-ins on path dependent debt trajectories, fueling 'structural polarization' between core and periphery.
Keywords: 330; performativity; potential output; path dependency; Eurozone crisis; fiscal policy; austerity